Examining the Frequency of Clinical and Paraclinical Symptoms in Opium Addicts Hospitalized Due to Lead Poisoning in Isfahan Province - Hamid Kalantari; Farzad Gheshlaghi; Marzieh Etezadi (Advanced Biomedical Research)
Background: Substance abuse and its consequences are major health hazards in the world. Opium addiction is a common form of substance abuse in Iran. The present study aims to examine the frequency of clinical and paraclinical symptoms of lead poisoning in opium users in the city of Isfahan. Materials and Methods: The current study is a cross-sectional study on patients with oral or inhaled consumption of opium or its derivatives, presenting with one of the clinical or laboratory symptoms of lead poisoning. Information related to the age and sex of the patients, duration and manner of opium consumption, clinical symptoms, and laboratory findings of patients were extracted from their files. Results: Three hundred opium user patients poisoned with lead were evaluated. 96.3% of the patients were men. The average age of the participants was 47.67 ± 11.57 years, and the average duration of opium use was 5.34 ± 6.95 years. The most frequent clinical symptom was abdominal pain (98%), followed by constipation (11.33%), nausea (9%), and vomiting (8.33%). 33.3% of people had an increase in AST, 17.1% of people had an increase in ALT, and 88.3% of people had an increase in ALP. Conclusion: We found that the most frequent clinical symptom was abdominal pain. 33.3% of people had an increase in AST, 17.1% of people had an increase in ALT, 88.3% of people had an increase in ALP and, 4% had an increase in creatine. Further studies are recommended.